Resveratrol biosynthesis, optimization, induction, bio-transformation and bio-degradation in mycoendophytes - Abo-Kadoum, M. A.; Abouelela, Mohamed E.; Al Mousa, Amal A.; Abo-Dahab, Nageh F.; Mosa, Mohamed A.; Helmy, Yosra A.; Hassane, Abdallah M. A. (Frontiers in Microbiology, 2022)
Resveratrol (3, 4, 5-trihydroxystilbene) is a naturally occurring polyphenolic stilbene compound produced by certain plant species in response to biotic and abiotic factors. Resveratrol has sparked a lot of interest due to its unique structure and approved therapeutic properties for the prevention and treatment of many diseases such as neurological disease, cardiovascular disease, diabetes, inflammation, cancer, and Alzheimer's disease. Over the last few decades, many studies have focused on the production of resveratrol from various natural sources and the optimization of large-scale production. Endophytic fungi isolated from various types of grapevines and P. cuspidatum, the primary plant sources of resveratrol, demonstrated intriguing resveratrol-producing ability. Due to the increasing demand for resveratrol, one active area of research is the use of endophytic fungi and metabolic engineering techniques for resveratrol large-scale production. The current review addresses an overview of endophytic fungi as a source for production, as well as biosynthesis pathways and relevant genes incorporated in resveratrol biosynthesis. Various approaches for optimizing resveratrol production from endophytic fungi, as well as their bio-transformation and bio-degradation, are described in detail.